2016
DOI: 10.1002/stem.2409
|View full text |Cite
|
Sign up to set email alerts
|

AKT Signaling Prevailing in Mesenchymal Stromal Cells Modulates the Functionality of Hematopoietic Stem Cells via Intercellular Communication

Abstract: The AKT pathway plays an important role in various aspects of stem cell biology. However, the consequences of constitutive activation of AKT in mesenchymal stromal cells (MSCs) on the fate of hematopoietic stem cells (HSCs) were unknown. Here, we show that bone marrow-derived MSCs expressing a constitutively active AKT1 expand HSCs, but severely affect their functionality. Conversely, stromal cells with silenced AKT1 limit HSC proliferation, but boost their functionality. These effects were related to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
6
20
0
Order By: Relevance
“…Taking clue from our previous study , we examined whether the rejuvenating factors are present in the EVs secreted by the MSCs. CM were subjected to ultra‐centrifugation (100,000 g ) and the pellets containing EVs were suspended in sterile medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking clue from our previous study , we examined whether the rejuvenating factors are present in the EVs secreted by the MSCs. CM were subjected to ultra‐centrifugation (100,000 g ) and the pellets containing EVs were suspended in sterile medium.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our earlier work , we speculated that perhaps aged MSCs possess activated AKT signaling and this could be the reason behind the loss of functionality in the aged HSCs. To examine this possibility, we subjected young and aged MSCs to Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the potential signalling pathway involved in the function of E2 to P3 hPDLSCs. It has been reported that PI3K/AKT signalling pathway plays a crucial role in stem cells self‐renewal, differentiation and stemness maintenance . Therefore, we focused on PI3K/AKT signalling pathway during E2 treatment in 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of functional and structural improvement of cardiac muscle after MSCs treatment remain unclear. It was originally assumed that MSCs differentiated into multiple cardiac cell types including cardiomyocytes, vascular endothelial cells, and vascular smooth muscle cells [38] .…”
Section: Isoproterenolmentioning
confidence: 99%